2003
DOI: 10.1530/eje.0.1480357
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal pituitary non-functioning adenoma with normal intra-sellar gland: massive tumor shrinkage on octreotide therapy

Abstract: Objective: Functioning or non-functioning ectopic tumors may develop from pharyngeal pituitary remnants. They constitute ,1% of all obstructive pharyngeal masses and they have a strong tendency to bleed. We report a case of a non-functioning ectopic pituitary adenoma of the rhino-pharynx studied over a long-term somatostatin analog treatment. Patient and treatment: A 60-year-old woman presented with severe posterior epistaxis. She had complained of nasal obstruction for the past 2 years. Magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…They arise from embryologic remnants along the path of migration of Rathke's pouch, which persist throughout the fetal and adult life (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They arise from embryologic remnants along the path of migration of Rathke's pouch, which persist throughout the fetal and adult life (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Other extracranial sites include the nasal cavity, mid-nasal ductus, nasopharynx (3,28,29), clivus (30)(31)(32)(33)(34)(35), sphenoid, ethmoid, petrous and temporal bone. The majority of the intracranial extrasellar EPAs are located in the suprasellar region (approximately 33%), usually contiguous with the pituitary stalk (28,36).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated positive effects of this therapy on tumor size, visual field disturbances, or excessive secretion of tumor products in patients harboring these tumors [41][42][43]. Like in acromegaly, some studies in clinically non-functioning pituitary adenomas have shown a positive correlation between pituitary uptake of 111 In-pentetreotide and the inhibition of tumor growth, or excessive hormonal secretion (like FSH, LH or glycoprotein hormone subunits in some patients), or the improvement in visual field defects by octapeptide somatostatin analog therapy [15,22,41,44]. Generally, negative 111 In-pentetreotide scintigraphy predicted failure of somatostatin analogs to produce any kind of response in these studies [15].…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 99%
“…Somatostatin analogues, being major inhibitors of cell growth, are used in a variety of clinical conditions related to the gastrointestinal tract, pancreas, neuroendocrine system, diabetic retinopathy, and thyroid eye disease [7 -9] . With regard to pituitary adenomas, therapy with somatostatin analogues has been eff ective, not only in GH secreting adenomas, but also in thyrotropin secreting pituitary adenomas [10] , in prolactinomas [11] , and in non-functioning, normotopic pituitary adenomas [12] .…”
Section: Introductionmentioning
confidence: 99%